2012
DOI: 10.1186/1471-2458-12-119
|View full text |Cite
|
Sign up to set email alerts
|

Non-hispanic whites have higher risk for pulmonary impairment from pulmonary tuberculosis

Abstract: BackgroundDisparities in outcomes associated with race and ethnicity are well documented for many diseases and patient populations. Tuberculosis (TB) disproportionately affects economically disadvantaged, racial and ethnic minority populations. Pulmonary impairment after tuberculosis (PIAT) contributes heavily to the societal burden of TB. Individual impacts associated with PIAT may vary by race/ethnicity or socioeconomic status.MethodsWe analyzed the pulmonary function of 320 prospectively identified patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
7
0
1
Order By: Relevance
“…Nonetheless, these data support the notion that under comparable conditions, TB outcomes after infection or treatment can be affected by host immune response genes; many of these genes can be segregated according continental ancestry (Baena et al, 2002;Zhivotovsky et al, 2003). We suspect that polymorphic gene variants responsible for TB immune function or those involved in xenobiotic metabolism, may differ significantly between racial/continental ancestries (Gumbo et al, 2007;Pasipanodya et al, 2012a;), and thus potentially contribute to PIAT. These findings suggest that difference in TB outcomes between ethnic/ geographically defined populations groups might have a biological as well as evolutionary basis.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Nonetheless, these data support the notion that under comparable conditions, TB outcomes after infection or treatment can be affected by host immune response genes; many of these genes can be segregated according continental ancestry (Baena et al, 2002;Zhivotovsky et al, 2003). We suspect that polymorphic gene variants responsible for TB immune function or those involved in xenobiotic metabolism, may differ significantly between racial/continental ancestries (Gumbo et al, 2007;Pasipanodya et al, 2012a;), and thus potentially contribute to PIAT. These findings suggest that difference in TB outcomes between ethnic/ geographically defined populations groups might have a biological as well as evolutionary basis.…”
Section: Discussionsupporting
confidence: 49%
“…Indeed, there is an association between phylogenetic lineage and clinical presentation and time-to-culture conversion in patients receiving standard anti-TB therapy (Click et al, 2012b,a;Nahid et al, 2010). There are known interethnic differences in the allele frequencies of enzymes responsible for metabolizing TB drugs that contributes to variable drug response (Pasipanodya et al, 2012a). Further study of these associations may identify appropriate treatments that can be tailored to specific lineages.…”
Section: Discussionmentioning
confidence: 99%
“…Important risk factors for airflow obstruction, including COPD, include smoking status, exposure to indoor and outdoor air pollution, occupational hazard, and infection [ 16 , 17 ]. Previous studies have indicated that pulmonary TB can lead to chronic airflow obstruction [ 4 , 7 , 18 20 ]. The Guangzhou Biobank Cohort Study in china reported that the prevalence of prior pulmonary TB was 24.2%, with an OR of 1.37 for the occurrence of airflow obstruction [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on chest X-rays (CXR) indicated that inactive TB lesions are associated with impaired pulmonary function [ 5 ]. Furthermore, a cohort study reported that pulmonary function deteriorates a few months after TB medication [ 7 ]. However, these studies were limited by small sample size, short-term observation, or inclusion of prior TB cases only assessed by CXR.…”
Section: Introductionmentioning
confidence: 99%
“…Se utiliza el concepto de vulnerabilidad social para enfocarse en ciertos grupos de personas, como la etnia, la condición socioeconómica (Pasipanodya et al, 2012), o que tienen modos de vida en sus espacios laborales y domésticos que favorecen la transmisión de la enfermedad y dificultan el acceso a la atención (Goldberg, 2012). El comportamiento espacial de la morbilidad y la mortalidad de las enfermedades respiratorias se ha asociado también con la contaminación ambiental y la privación material en el caso de la Enfermedad Pulmonar Obstructiva Crónica (EPOC) (Chan, Chian, Ming Daw, Hsuan-wen, y Shi-yung Liu, 2014) Las barreras geográficas y socioeconómicas para el acceso al tratamiento determina la prevalencia de la tuberculosis en primer lugar, pero también nuevos casos y su letalidad (Mauch et al, 2011).…”
unclassified